PENGGUNAAN SENSUALITAS DALAM KOMUNIKASI PEMASARAN SEBUAH STUDI KASUS PADA PARIWARA TELEVISI IKLAN KONDOM SUTRA - Yusnaidi Yusnaidi; Cut Devi Maulidasari; Fajri Hadi; Fatmayanti Fatmayanti; Muhammad Rahmat Hidayat (universitas teuku umar, 2019)
This research is designed to anylize the used of women sexuality at tv advertising. It is a fact that tv ad is one of the effective marketing communication tools to promotes a product and builds corporate image. However there are a lot of misconduct in implementing tv ads to persuade consumers by showing conversations and scenes with a lot of sexual images. Sexual images in the ads are happened in many marketing events and programs. It has been considered as the effective approach to attract consumers attention and the message would be easy to be remembered and internalized in the memory. This phenomena also had happened in Indonesia where tv ads content sexual images which had caused controversy and rejection among the consumers and authorities. There were feminism issues about the women that should not be treated as the sexual object. The sample of tv ads which content sexual images in Indonesia was the ad of Condom Sutra performing four artist playing bilyard. This tv ads had appeared on the national tv channel in 2015 and had a lot of sexual languages, images and the moves that could be considered as pornographic actions. There were several researchs had been conduct on this particular issue but this research presents the analysis through different point of view. Therefore the semiotic analyzing methods introduced by Roland Barthes is applied in this research paper. The observations methods and qualitative research approach are part of the analyzing process to reach the objective and conclude the phenomena.Keywords : condom sutra, tv ads, sexual image.